A Note on Popular Baby Names on the Social Security Website: An Important Onomastic Resource. (2nd January 2017) - Nuessel, Frank
Abstract : This note provides a road map for the use of the Social Security "Popular Baby Names" website. It gives information on how to navigate the site and utilize all of its features for research, decision making in the selection of a baby's name, personal information, and many other possibilities.